The Effect of Pilates Exercise on Reducing Menstrual Pain in Adolescents: Literature Study - Eva Zulisa; Esa Zahirah; Lenny Irmawaty Sirait; Eva Sri Rahayu; Inna Noor Inayati (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Dysmenorrhea, or menstrual pain, is common among adolescents, with global prevalence rates reaching 59.7% to 92%. This pain, affecting the lower abdomen, back, and groin, usually begins 24 hours before menstruation and can last up to three days. Management includes pharmacological options like NSAIDs and analgesics, as well as non-pharmacological approaches. Pilates exercise is a practical, non-drug option shown to reduce menstrual pain by stimulating endorphin production, providing a natural sense of relief and comfort. Purposes : The goal of this study is to ascertain whether Pilates exercises can help adolescents who are experiencing menstrual pain. Methods : The design of this study is a literature review. Search for published articles on Google Scholar, Pubmed and GARUDA with the keywords "Pilates Exercise", "Dysminorhea / Menstrual pain". Of the three databases found 446 articles, executed as many as 432 because they did not match the research variables so that 9 articles were obtained to be read in full and 5 articles were found that met the criteria. Results: The results of the literature review of 5 literature studies conducted stated that there was an effect of pilates exercise on reducing menstrual pain in adolescents. Implications : Pilates exercise can be an effective and safe non-pharmacological treatment alternative to reduce menstrual pain in adolescent girls. Conclusion : It is hoped that pilates exercises can be recommended as an effective method in efforts to reduce menstrual pain in adolescents.